TB Specimen Transportation Model as a Strategy for Increasing Service Access through Toss-TBC - Ivy Violan Lawalata; Bellytra Talarima (Newinera Publisher, 2022)
The proportion of TB RO cases in 2015 was 228 cases, an estimated 2% of new TB cases were 5 cases and 12% of TB re-treatment cases were RO TB cases. access to TB services through island-based TOSS-TB in Ambon City in 2022. This research is a descriptive study with an observational approach and a SWOT analysis using a qualitative SWOT matrix to analyze internal and external factors on the subject and research object, which will then be used to design a model transport of TB specimens. The research results obtained an overview of the TB specimen transportation system network system in Ambon City in 2022 3 health centers TCM laboratory with a network system, there are 19 health centers, TB specimen referral mechanism at the Ambon City Health Service in 2022 carried out by 19 Referral Health Centers, Test examples from aspects of packaging and Referrals at the Ambon City Health Office in 2022 are carried out by 19 Community Health Centers as referral health centers for the process of sending specimens to the TCM Laboratory and Reviewing and analyzing aspects of examination results reporting in the framework of the City of Ambon City Health Service 2022 online using Form TB 05 from the TCM Laboratory Health Center to the Referral Health Center.